Active surveillance of 2017 seasonal influenza vaccine safety: An observational cohort study of individuals aged 6 months and older in Australia - Pillsbury, A.; Glover, C.; Jacoby, P.; Quinn, H.; Fathima, P.; Cashman, P.; Leeb, A.; Blyth, C.; Gold, M.; Snelling, Thomas; Macartney, K. (BM J Group, 2018)
© Author(s) (or their employer(s)) 2018. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ. Objective To actively solicit adverse events experienced in the days following immunisation with quadrivalent inactivated influenza vaccine using Australia's near real-time, participant-based vaccine safety surveillance system, AusVaxSafety. Design and setting Observational cohort study conducted in 194 sentinel surveillance immunisation sites (primary care, hospital and community-based clinics) across Australia. Participants Individuals aged =6 months who received a routine seasonal influenza vaccine at a participating site (n=102 911) and responded to a survey (via short message service or email) sent 3 days after vaccination about adverse events experienced (n=73 892; 71.8%). Main outcome measure Near real-time and cumulative participant-reported rates of any adverse event, fever or medical attendance experienced within 3 days after vaccination overall, by brand, age, pregnancy status and concomitant vaccine receipt. Results Participant median age was 57 years (range: 6 months to 102 years); 58.1% (n=42 869) were female and 2.7% (n=2018) were pregnant. Near real-time fast initial response cumulative summation and Bayesian analyses of weekly event rates did not demonstrate a safety signal. Children aged 6 months to 4 years had higher event rates (522/6180; 8.4%) compared with older ages; participants aged =65 years reported fewer events (1695/28 154; 6.0%). There were no clinically significant differences in safety between brands, by age group or overall. Cumulative data analysis demonstrated that concomitant vaccination was associated with increased rates of fever (2.1% vs 0.8%) and medical attendance (0.8% vs 0.4%), although all rates were low and did not exceed expected levels. Conclusions Novel, postmarketing AusVaxSafety surveillance demonstrated comparable and expected safety outcomes for the 2017 quadrivalent inactivated influenza vaccine brands used in Australia. These near real-time, participant-reported data are expected to encourage confidence in vaccine safety and promote uptake.